Pollen grains and seed-morphology as related to Biochemical Patterns in five species of genus Ocimum L (Lamiaceae Juss.) of Saudi Arabia - kasem, wael taha (Journal of Phytology, 2017)
This study aims to investigate the pollen and seed characters by light microscopy (LM) and scanning electron microscope (SEM) as related to biochemical data of seed protein and esterase isoenzymes by SDS-PAGE technique in the five Saudi Arabian Ocimum L. species. The detailed description for pollen and seed in addition electrophoretic patterns were conducted by means of numerical analyses based on thirty-nine parameters. The pollen grains were zonocolpate, hexacolpate, prolate to subprolate. Three types of exine ornamentation were recognized, perforate, reticulate and granulate. Also, Â The periclinal, the anticlinal and the boundaries between cells are described by the aid of SEM which exhibited four main distinct types of nutlets sculpture undulate, quirky, circular and straight. Molecular patterns of protein profiles and esterase (EC.3.1.1.1) showed that esterase could be considered as positive markers than protein, minimum and maximum gene / gene expression of esterase isoenzymes are demonstrated. The relationships between the studied taxa were demonstrated as a phenogram.Â